2022
DOI: 10.2174/1573401318666220120105931
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk and Human Papillomavirus Infection: A Bradford Hill Criteria Based Evaluation

Abstract: Background: The association between human papillomavirus (HPV) and human breast cancer (BC) has already been thoroughly studied worldwide with contradictory findings. Although the researchers have tried to minimize the conflict using statistical meta-analysis, because of its shortcomings, there is still a need to evaluate the correlation between HPV and BC using any additional method. Objectives: This study was launched to investigate the correlation between HPV and BC through the application of Bradford Hil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genome (KEGG) pathway enrichment analysis were used to identify the efficacy of genes. In this study, the application of the clusterProfiler package in the RStudio software device to the corresponding differences in the overall survival of breast cancer shows that the gene holds GO elaboration and KEGG elaboration; P < 0.05 is considered to have statistical significance ( Figure 1 ) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genome (KEGG) pathway enrichment analysis were used to identify the efficacy of genes. In this study, the application of the clusterProfiler package in the RStudio software device to the corresponding differences in the overall survival of breast cancer shows that the gene holds GO elaboration and KEGG elaboration; P < 0.05 is considered to have statistical significance ( Figure 1 ) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…With a diverse clinical spectrum ranging from indolent to aggressive forms, UCEC poses signifi-cant health challenge [9,10]. While early-stage UCEC is often associated with a favorable prognosis, a subset of cases manifests as highgrade tumors with aggressive behavior, necessitating a deeper understanding of the underlying molecular mechanisms that drive its progression [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of HPV in malignant breast tumors has been reported, indicating a potential role of HPV in the early stage of breast cancer and breast carcinogenesis [7][8][9][10][11]. The existence of a causal link between HPV infection and breast cancer is still subject to debate; while some research revealed a higher risk consistent with a possible role of HPV in the development of breast cancer [5,8,10,[12][13][14][15][16][17][18], other studies found no such association [19][20][21][22][23][24]. Data, however, is limited in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%